Phosphor powder, composite body and light-emitting device

A fluorescent powder with controlled absorption peaks and optimized manufacturing process addresses reliability issues in white LEDs, ensuring high fluorescence intensity and stability.

JP2025015272APending Publication Date: 2025-01-30DENKA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023118583
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Existing fluorescent powders used in white LEDs, such as CASN and SCASN, face reliability issues due to high absorption peaks in their infrared spectra, which affect their performance and longevity.

Method used

The development of a fluorescent powder comprising CASN and SCASN particles with controlled Kubelka-Munk function values for absorption peaks, optimized moisture content, and specific crystal structure to enhance reliability, using a manufacturing process that includes firing, annealing, and acid treatment to improve performance.

Benefits of technology

The resulting fluorescent powder exhibits improved reliability with reduced absorption peaks, maintaining high fluorescence intensity and stability under pressure cooker tests, enhancing the performance of white LEDs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015272000001_ABST
    Figure 2025015272000001_ABST
Patent Text Reader

Abstract

To provide phosphor powder with improved reliability.SOLUTION: There is provided phosphor powder containing one or more phosphor particles selected from the group consisting of CASN phosphor particles and SCASN phosphor particles. A phosphor powder has an absorption peak a in the wavenumber region of 3200 cm-1 or more and less than 3350 cm-1 in the infrared absorption spectrum of the Kubelka-Munk function value (KM value) obtained by FT-IR measurement of the phosphor powder, and a KM value of the absorption peak a is 1.25 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a phosphor powder, a composite, and a light-emitting device. [Background technology]

[0002] In order to manufacture white LEDs, research is being conducted on red phosphors that convert the blue light from a blue LED chip into red light. Known red phosphors include CASN phosphors and SCASN phosphors. In Patent Document 1, a nitride phosphor having a general formula M is disclosed for the purpose of providing a nitride phosphor having excellent luminescence characteristics even when excited with high-density light, particularly a narrow half-width of the emission spectrum, and a high luminescence quantum efficiency maintenance rate. a Sr b Ca c Al d S e N f It contains a crystalline phase represented by 4000 mW / mm 2 The phosphor is characterized by having a quantum efficiency maintenance rate of 85% or more when excited by light. In this general formula, M represents an activation element, and 0 <a<0.05、0.95≦b≦1、0≦c<0.1、a+b+c=1、0.7≦d≦1.3、0.7≦e≦1.3、2.5≦f≦3.5である。 [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-077800 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a phosphor powder with improved reliability, and a composite body and a light emitting device using the phosphor powder with improved reliability. [Means for solving the problem]

[0005] The present inventors have conducted extensive research to solve the above problems. As a result, a phosphor having a wavelength of 3200 cm or more in an infrared absorption spectrum of a Kubelka-Munk function value (KM value) measured by FT-IR measurement is obtained. -1 More than 3350cm -1 The inventors have found that a phosphor powder having an absorption peak a in a wave number region less than 1.5 and a KM value of the absorption peak a of 1.25 or less can improve reliability, and have completed the present invention.

[0006] According to the present invention, there are provided the following phosphor powder, composite body, and light emitting device.

[0007] [1] A phosphor powder comprising one or more phosphor particles selected from the group consisting of CASN phosphor particles and SCASN phosphor particles, In the infrared absorption spectrum of the phosphor powder, the Kubelka-Munk function value (KM value) measured by FT-IR measurement is 3200 cm -1 More than 3350cm -1 has an absorption peak a in a wave number region less than The phosphor powder has a KM value of the absorption peak a of 1.25 or less. [2] In the infrared absorption spectrum, the value of the Kubelka-Munk function (KM value) is 3350 cm -1 More than 3450cm -1 Further having an absorption peak b in the following wave number region, The phosphor powder according to [1], wherein the KM value of the absorption peak b is 1.24 or less. [3] The phosphor powder according to [2], wherein A>B is satisfied when the KM value of the absorption peak a is A and the KM value of the absorption peak b is B. [4] The phosphor powder according to any one of [1] to [3], wherein the phosphor powder has a moisture content of 0.38 mass % or less, obtained by the following method 1. (Method 1) Using a Karl Fischer moisture measuring device and a moisture vaporizing device, the mass (mg) of water generated from the phosphor powder when heated to 400 °C under the condition of a nitrogen gas flow rate of 300 mL / min is measured by the coulometric titration method in accordance with JIS K 0068:2001. Next, the water content rate is determined with respect to when the total amount of the phosphor powder is 100% by mass, and this is taken as the moisture content (mass%). [5] General formula, Eu a Sr b Ca c Al d Si e N f O g A phosphor powder according to any one of [1] to [4], comprising phosphor particles represented by the following formula, where 0 < a < 1.00, 0 < b < 1.00, 0 < c < 1.00, 0.70 < a + b + c < 1.30, 0.70 < d < 1.30, 0.70 < e < 1.30, 0 < f < 3.00, 0 < g < 3.00, and 2.50 < f + g < 3.50. [6] The phosphor powder according to [5], where a < 0.30. [7] The phosphor powder according to [5] or [6], where b > 0.50. [8] The phosphor powder according to any one of [5] to [7], where the molar ratio of b / (b + c) of the phosphor powder is 0.96 or more and 0.99 or less. [9] The volume-based median diameter D of the phosphor powder by the laser diffraction scattering method 50 is 1 μm or more and 40 μm or less, and the phosphor powder according to any one of [1] to [8].

[10] The phosphor powder according to any one of [1] to [9], where the relative fluorescence intensity reduction rate of the phosphor powder by the following Method 2 is 10.0% or less. (Method 2) The relative fluorescence intensity of the phosphor powder measured using a spectrophotometer is defined as Y1 (%), and the relative fluorescence intensity of the phosphor powder after 5 g of the phosphor powder is kept for 53 hours under an atmosphere of 130°C, relative humidity of 98%, and 0.16 MPaG using a pressure cooker tester is defined as Y2 (%), where 100 × (Y1-Y2) / Y1 is the relative fluorescence intensity reduction rate (%).

[11] The phosphor powder according to

[10] , wherein Y1 is 150% or more.

[12] The phosphor powder according to any one of [1] to

[11] , wherein the phosphor powder has an absorptivity decrease rate of 5.0% or less for light having a wavelength of 455 nm, according to the following method 3. (Method 3) The absorptance of the phosphor powder for light with a wavelength of 455 nm measured using a spectrophotometer is defined as Z1 (%), and the absorptance of the phosphor powder for light with a wavelength of 455 nm after 5 g of the phosphor powder is held for 53 hours in an atmosphere of 130°C, relative humidity of 98%, and 0.16 MPaG using a pressure cooker tester is defined as Z2 (%), where 100 × (Z1 - Z2) / Z1 is the absorptance reduction rate (%).

[13] The phosphor powder according to

[12] , wherein Z1 is 90.0% or more.

[14] A composite comprising: a phosphor powder according to any one of [1] to

[13] ; and a sealant that seals the phosphor powder.

[15] The composite according to

[14] , wherein the sealing material contains one or more selected from the group consisting of a silicone resin, an epoxy resin, a urethane resin, glass, and ceramics.

[16] A light emitting element that emits excitation light; A complex according to

[14] or

[15] , which converts the wavelength of the excitation light; A light emitting device comprising: Effect of the Invention

[0008] According to the present invention, it is possible to provide a phosphor powder with improved reliability, and a composite body and a light emitting device using the phosphor powder with improved reliability. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the structure of a light-emitting device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. In the drawings, similar components are given similar symbols and descriptions thereof will be omitted as appropriate. In order to avoid complexity, when there are multiple identical components in the same drawing, only one of them may be labeled with a reference symbol, and not all of them. The drawings are for illustrative purposes only. The shapes and dimensional ratios of the components in the drawings do not necessarily correspond to the actual products.

[0011] In this embodiment, the numerical range "A to B" indicates A or more and B or less, unless otherwise specified.

[0012] <Phosphor powder> The phosphor powder of the present embodiment contains one or more phosphor particles selected from the group consisting of CASN phosphor particles and SCASN phosphor particles. From the viewpoint of further improving the fluorescent properties of the phosphor powder, the phosphor powder of the present embodiment preferably contains SCASN phosphor particles.

[0013] The CASN phosphor particles of this embodiment are composed of (Si,Al)-N4 regular tetrahedrons bonded together, with Ca atoms located in the gaps between the skeletons. 2+ A part of Eu acts as a luminescence center. 2+ These are phosphor particles in which an activator element such as ZnO is substituted. The SCASN phosphor particles of this embodiment are composed of (Si,Al)-N4 regular tetrahedrons bonded together, and some of the Ca atoms located in the gaps of the skeleton are replaced with Sr atoms to form a solid solution. 2+ A part of Eu acts as a luminescence center. 2+ These are phosphor particles in which an activator element such as ZnO is substituted.

[0014] The phosphor powder of this embodiment has a peak at 3200 cm in the infrared absorption spectrum of the Kubelka-Munk function value (KM value) measured by FT-IR. -1 More than 3350cm -1 and the KM value of the absorption peak a is 1.25 or less.

[0015] In this specification, the "value of the Kubelka-Munk function" refers to a function that converts the reflectance of a substance into a value that is an index of the absorption specific to the substance, and can be obtained by dividing the extinction coefficient by the scattering coefficient (extinction coefficient / scattering coefficient). In this specification, the term "absorption peak" refers to the maximum peak in a specific wave number region in the infrared absorption spectrum of the Kubelka-Munk function value (KM value). Infrared absorption spectrum of Kubelka-Munk function value (KM value) by FT-IR measurement can identify functional groups etc. from the wave number value.

[0016] According to the investigations of the present inventors, it has been found that there is a correlation between the KM value of the absorption peak a of a phosphor powder and the reliability of the phosphor powder. As a result of further investigations by the inventors based on the above findings, it was found that the infrared absorption spectrum of the Kubelka-Munk function value (KM value) of the phosphor powder measured by FT-IR has a peak at 3200 cm -1 More than 3350cm -1 The inventors have found that the reliability of phosphor powder can be improved by using the KM value of absorption peak a present in the wave number range less than 1.25 as an index and setting the KM value of absorption peak a to 1.25 or less, thereby completing the present invention.

[0017] From the viewpoint of further improving the reliability of the phosphor powder, the KM value of the absorption peak a of the phosphor powder of this embodiment is preferably 0.01 or more, more preferably 0.10 or more, even more preferably 0.15 or more, even more preferably 0.20 or more, even more preferably 0.25 or more, even more preferably 0.40 or more, even more preferably 0.60 or more, and is 1.25 or less, preferably 1.20 or less, more preferably 1.15 or less, even more preferably 1.10 or less, even more preferably 1.05 or less, and even more preferably 1.00 or less.

[0018] From the viewpoint of further improving the reliability of the phosphor powder, the phosphor powder of this embodiment has an infrared absorption spectrum of the Kubelka-Munk function value (KM value) measured by FT-IR measurement, preferably having a peak at 3350 cm -1 More than 3450cm -1 It has an absorption peak b in the following wave number region.

[0019] From the viewpoint of further improving the reliability of the phosphor powder, the KM value of the absorption peak b of the phosphor powder of this embodiment is preferably 0.01 or more, more preferably 0.10 or more, even more preferably 0.15 or more, even more preferably 0.20 or more, even more preferably 0.25 or more, even more preferably 0.40 or more, even more preferably 0.60 or more, and is preferably 1.24 or less, more preferably 1.20 or less, even more preferably 1.15 or less, even more preferably 1.10 or less, even more preferably 1.05 or less, even more preferably 1.00 or less, and even more preferably 0.95 or less.

[0020] From the viewpoint of further improving the reliability of the phosphor powder of this embodiment, when the KM value of absorption peak a is A and the KM value of absorption peak b is B, preferably A>B is satisfied.

[0021] In this embodiment, the infrared absorption spectrum of the Kubelka-Munk function value (KM value) of the phosphor powder can be measured by, for example, weighing out about 50 mg of the phosphor powder, filling it into a measuring cup without diluting it, and using a Fourier transform infrared spectrometer by a diffuse reflectance method.

[0022] The moisture content of the phosphor powder of this embodiment, as measured by coulometric titration (Karl Fischer titration), is, from the viewpoint of further improving the reliability of the phosphor powder, preferably 0.01 mass% or more, more preferably 0.05 mass% or more, even more preferably 0.10 mass% or more, even more preferably 0.20 mass% or more, even more preferably 0.25 mass% or more, and is preferably 0.38 mass% or less, more preferably 0.37 mass% or less, even more preferably 0.36 mass% or less, and even more preferably 0.35 mass% or less.

[0023] In this embodiment, the moisture content of the phosphor powder can be measured, for example, by the following method. First, using a Karl Fischer moisture analyzer and a moisture vaporizer, the mass (mg) of water generated from the phosphor powder when heated to 400°C under conditions of a nitrogen gas flow rate of 300 mL / min is measured by coulometric titration in accordance with JIS K 0068: 2001. Next, the water content is calculated when the total amount of the phosphor powder is taken as 100% by mass, and this is taken as the moisture content (% by mass).

[0024] As another index for further improving the reliability of the phosphor powder, it is more preferable that the phosphor powder of this embodiment has an oxygen content increase rate of 100% or more and 500% or less before and after the pressure cooker test. Here, the oxygen increase rate is calculated by 100×X2 / X1, where X1 (mass%) is the oxygen content of the phosphor powder, and X2 (mass%) is the oxygen content of the phosphor powder after 5 g of the phosphor powder is held at 130° C., under a relative humidity of 98% and a pressure of 0.16 MPaG for 53 hours using a pressure cooker tester.

[0025] From the viewpoint of further improving the reliability of the phosphor powder, the oxygen content increase rate of the phosphor powder of this embodiment is preferably 100% or more, more preferably 101% or more, even more preferably 103% or more, and is preferably 500% or less, more preferably 460% or less, even more preferably 430% or less, even more preferably 400% or less, even more preferably 380% or less, even more preferably 350% or less, even more preferably 300% or less, even more preferably 250% or less, even more preferably 200% or less, even more preferably 180% or less.

[0026] From the viewpoint of further improving the reliability of the phosphor powder, the oxygen content X1 of the phosphor powder of this embodiment is preferably 0.10 mass% or more, more preferably 0.50 mass% or more, even more preferably 1.00 mass% or more, even more preferably 1.30 mass% or more, even more preferably 1.50 mass% or more, and is preferably 5.00 mass% or less, more preferably 4.00 mass% or less, even more preferably 3.50 mass% or less, even more preferably 3.00 mass% or less, even more preferably 2.50 mass% or less, and even more preferably 2.40 mass% or less. From the viewpoint of further improving the reliability of the phosphor powder, the oxygen content X2 of the phosphor powder after the pressure cooker test of this embodiment is preferably 0.10 mass% or more, more preferably 0.50 mass% or more, even more preferably 1.00 mass% or more, even more preferably 1.30 mass% or more, and even more preferably 1.50 mass% or more, and is preferably 12.00 mass% or less, more preferably 11.00 mass% or less, even more preferably 10.00 mass% or less, even more preferably 9.50 mass% or less, even more preferably 9.00 mass% or less, even more preferably 7.00 mass% or less, even more preferably 5.00 mass% or less, and even more preferably 4.00 mass% or less.

[0027] In this embodiment, the oxygen content (mass %) of the phosphor powder can be obtained, for example, by weighing out 0.03 g of the phosphor powder and measuring the oxygen content with an oxygen / nitrogen analyzer.

[0028] As another index for further improving the reliability of the phosphor powder, the phosphor powder of the present embodiment has a color difference ΔE * It is more preferable that the value is 25.0 or less. Here, the color difference ΔE * When a pressure cooker test was conducted using a pressure cooker tester in which 5 g of phosphor powder was exposed to an atmosphere of 130°C, 98% relative humidity, and 0.16 MPa for 53 hours, the CIE1976L * a * b * The chromaticity coordinates (L1 * , a1 * , b1 * ) and the chromaticity coordinates (L2 * , a2 * , b2 * ) and is calculated using the following formula: ΔE * ={(L1 * -L2 * ) 2 +(a1 * -a2 * ) 2 +(b1 * -b2 * ) 2} 1 / 2

[0029] Color difference ΔE of the phosphor powder of this embodiment * From the viewpoint of further improving the reliability of the phosphor powder, is preferably 0.0 or more, more preferably 0.5 or more, even more preferably 1.5 or more, even more preferably 2.0 or more, even more preferably 2.5 or more, and is preferably 25.0 or less, more preferably 23.0 or less, even more preferably 21.0 or less, even more preferably 20.0 or less, even more preferably 19.0 or less, even more preferably 17.0 or less, even more preferably 15.0 or less, even more preferably 12.0 or less, even more preferably 10.0 or less, even more preferably 8.0 or less, even more preferably 7.0 or less.

[0030] The phosphor powder of this embodiment (L1* -L2 * ) 2 From the viewpoint of further improving the reliability of the phosphor powder, is preferably 0.0 or more, more preferably 0.1 or more, and is preferably 65.0 or less, more preferably 50.0 or less, even more preferably 40.0 or less, even more preferably 30.0 or less, even more preferably 25.0 or less, even more preferably 20.0 or less, even more preferably 15.0 or less, even more preferably 10.0 or less, even more preferably 5.0 or less, even more preferably 2.0 or less, and even more preferably 1.0 or less.

[0031] The phosphor powder of this embodiment (a1 * -a2 * ) 2 From the viewpoint of further improving the reliability of the phosphor powder, is preferably 0.0 or more, more preferably 0.1 or more, even more preferably 0.3 or more, and is preferably 260.0 or less, more preferably 220.0 or less, even more preferably 150.0 or less, even more preferably 100.0 or less, even more preferably 50.0 or less, even more preferably 10.0 or less, even more preferably 5.0 or less, even more preferably 4.0 or less.

[0032] The phosphor powder of this embodiment (b1 * -b2 * ) 2 From the viewpoint of further improving the reliability of the phosphor powder, is preferably 0.0 or more, more preferably 0.5 or more, even more preferably 1.0 or more, and is preferably 300.0 or less, more preferably 250.0 or less, even more preferably 200.0 or less, even more preferably 150.0 or less, even more preferably 120.0 or less, even more preferably 100.0 or less, even more preferably 90.0 or less, even more preferably 70.0 or less, even more preferably 50.0 or less, even more preferably 40.0 or less, even more preferably 30.0 or less.

[0033] In this embodiment, the color difference ΔE * The method for measuring the amount of β-amino acid is, for example, as follows. First, using a color difference meter, the CIE1976L color of the phosphor powder was measured under the conditions of C light source and 2° field of view. * a * b * Chromaticity coordinates (L1 * , a1 * , b1 * Next, a pressure cooker test was performed in which 5 g of phosphor powder was exposed to an atmosphere of 130°C, 98% relative humidity, and 0.16 MPa for 53 hours. The CIE1976L * a * b * Chromaticity coordinates (L2 * , a2 * , b2 * ) is measured in the same manner. Next, based on the measured values ​​of each chromaticity coordinate, (L1 * -L2 * ) 2 , (a1 * -a2 * ) 2 and (b1 * -b2 * ) 2 Then, ΔE is calculated using the following formula: * Calculate. ΔE * ={(L1 * -L2 * ) 2 +(a1 * -a2 * ) 2 +(b1 * -b2 * ) 2} 1 / 2

[0034] The phosphor powder of the present embodiment can be obtained by appropriately selecting the raw materials, the usage ratio of each raw material, the manufacturing procedure, the manufacturing conditions, and the like. Regarding the selection of raw materials and the quantitative ratio of raw materials, preferably, a Sr-containing raw material is used in a larger amount, and a "core" described later is added. Regarding the manufacturing procedure and manufacturing conditions, preferably, atmospheric heat treatment is performed under appropriate conditions, firing and annealing are performed using a sealed container, and the like. These details will be described later.

[0035] (Crystal structure, elemental composition, etc.) The phosphor particles of the present embodiment are composed of phosphor particles represented by the general formula Eu having the same crystal phase as CaAlSiN3 a Sr b Ca c Al d Si e N f O g In this general formula, 0 < a < 1.00, 0 < b < 1.00, 0 < c < 1.00, 0.70 < a + b + c < 1.30, 0.70 < d < 1.30, 0.70 < e < 1.30, 0 < f < 3.00, 0 < g < 3.00, 2.50 < f + g < 3.50.

[0036] The crystal phase can be confirmed by powder X-ray diffraction. A single crystal phase of the crystal is preferable for the crystal phase, but as long as it does not have a great influence on the phosphor characteristics, it may contain different phases. The presence or absence of different phases can be determined, for example, by the presence or absence of peaks other than those due to the target crystal phase by powder X-ray diffraction.

[0037] Regarding a, from the viewpoint of improving the fluorescence characteristics of the phosphor powder, preferably 0.01 < a, more preferably 0.03 < a, still more preferably 0.05 < a, still more preferably 0.06 < a, still more preferably 0.07 < a, and preferably a < 0.30, more preferably a < 0.25, still more preferably a < 0.20, still more preferably a < 0.15, still more preferably a < 0.10.

[0038] Regarding b, from the perspective of improving the fluorescence characteristics of the phosphor powder, preferably 0.50 < b, more preferably 0.60 < b, still more preferably 0.70 < b, still more preferably 0.80 < b, still more preferably 0.83 < b, and preferably b < 0.99, more preferably b < 0.95, still more preferably b < 0.90.

[0039] As another index from the perspective of "a large amount of Sr", the molar ratio of b / (b + c) is preferably 0.96 or more, more preferably 0.97 or more, still more preferably 0.98 or more, from the perspective of improving the fluorescence characteristics of the phosphor powder, and preferably 0.99 or less.

[0040] Regarding c, from the perspective of improving the fluorescence characteristics of the phosphor powder, 0 < c, and preferably c < 0.20, more preferably c < 0.15, still more preferably c < 0.10, still more preferably c < 0.05, still more preferably c < 0.03.

[0041] Regarding d, from the perspective of improving the fluorescence characteristics of the phosphor powder, preferably 0.80 < d, more preferably 0.85 < d, still more preferably 0.90 < d, still more preferably 0.95 < d, and preferably d < 1.20, more preferably d < 1.15, still more preferably d < 1.10, still more preferably d < 1.05.

[0042] Regarding e, from the perspective of improving the fluorescence characteristics of the phosphor powder, preferably 0.75 < e, more preferably 0.80 < e, still more preferably 0.85 < e, still more preferably 0.90 < e, and preferably e < 1.20, more preferably e < 1.10, still more preferably e < 1.05, still more preferably e < 1.00, still more preferably e < 0.97.

[0043] Regarding f, from the viewpoint of improving the fluorescence characteristics of the phosphor powder, preferably 2.55 < f, more preferably 2.60 < f, still more preferably 2.65 < f, still more preferably 2.70 < f, still more preferably 2.75 < f, and preferably f < 3.40, more preferably f < 3.20, still more preferably f < 3.10, still more preferably f < 3.00, still more preferably f < 2.90, still more preferably f < 2.85, still more preferably f < 2.82.

[0044] Regarding g, from the viewpoint of improving the fluorescence characteristics of the phosphor powder, preferably 0.01 < g, more preferably 0.05 < g, still more preferably 0.10 < g, still more preferably 0.15 < g, and preferably g < 0.80, more preferably g < 0.50, still more preferably g < 0.40, still more preferably g < 0.35, still more preferably g < 0.30, still more preferably g < 0.25.

[0045] In the present embodiment, among the molar ratios of the respective elements contained in the phosphor powder, the molar ratios of Eu, Sr, Ca, Al, and Si can be measured, for example, by dissolving the phosphor powder by a pressurized acid decomposition method, preparing a sample solution, and performing quantitative analysis of the elements on the obtained sample solution using an ICP emission spectroscopic analyzer. In the present embodiment, among the molar ratios of the respective elements contained in the phosphor powder, the molar ratios of N and O can be obtained, for example, by weighing 0.03 g of the phosphor powder and measuring the contents of oxygen and nitrogen using an oxygen / nitrogen analyzer.

[0046] (Median diameter D 50 ) The median diameter D of the phosphor particles of the present embodiment 50From the viewpoint of further improving the reliability of the phosphor powder, the median diameter is preferably 1 μm or more, more preferably 5 μm or more, even more preferably 10 μm or more, even more preferably 15 μm or more, even more preferably 17 μm or more, even more preferably 20 μm or more, and is preferably 40 μm or less, more preferably 36 μm or less, even more preferably 33 μm or less, even more preferably 30 μm or less. In applications for converting blue light from a blue LED to red light, a median diameter of this order is preferable in terms of the balance of various performances such as brightness, conversion efficiency, and reliability.

[0047] In this embodiment, the median diameter D 50 can be measured as a volume-based value, for example, by a laser diffraction scattering method. Median diameter D 50 The adjustment of can be carried out by appropriately applying known means such as pulverization, sieving, etc. The details will be described later.

[0048] (Absorption rate) The absorptance Z1 of the phosphor powder of this embodiment for light with a wavelength of 455 nm is, from the viewpoint of further improving the performance balance of the reliability and fluorescent properties of the phosphor powder, preferably 90.0% or more, more preferably 92.0% or more, even more preferably 94.0% or more, even more preferably 95.0% or more, and is preferably 99.9% or less, more preferably 99.0% or less, even more preferably 98.0% or less.

[0049] In this embodiment, the absorptance Z1 of the phosphor powder with respect to light having a wavelength of 455 nm can be determined, for example, by the following method. First, the phosphor powder is filled into a concave cell so that the surface is smooth, and then the cell is attached to the opening of an integrating sphere. Next, monochromatic light with a wavelength of 455 nm is split from a Xe lamp, which is a light source, and introduced into the integrating sphere using an optical fiber as excitation light for the phosphor. The phosphor powder is irradiated with this monochromatic excitation light, and the fluorescence spectrum is measured using a spectrophotometer. From the obtained fluorescence spectrum data, the emission intensity of the phosphor powder is determined, and the number of excitation reflected light photons (Qref) and the number of fluorescence photons (Qem) are calculated. The number of excitation reflected light photons is calculated in the wavelength range of 450 to 465 nm, and the number of fluorescence photons is calculated in the range of 465 to 800 nm. In addition, using the same device, a standard reflector with a reflectance of 99% (Spectralon (registered trademark), manufactured by Labsphere) is attached to the opening of the integrating sphere to measure the spectrum of excitation light with a wavelength of 455 nm. At this time, the number of excitation light photons (Qex) is calculated from the spectrum in the wavelength range of 450 to 465 nm. From the above calculation results, the absorptance Z1 of the phosphor for 455 nm light is calculated based on the following formula. Absorption rate for 455 nm light Z1 = ((Qex-Qref) / Qex) x 100

[0050] (internal quantum efficiency) The internal quantum efficiency of the phosphor powder of this embodiment when excited by light with a wavelength of 455 nm is, from the viewpoint of further improving the performance balance of the reliability and fluorescent properties of the phosphor powder, preferably 60.0% or more, more preferably 64.0% or more, even more preferably 67.0% or more, even more preferably 70.0% or more, and preferably 99.0% or less, more preferably 90.0% or less, even more preferably 85.0% or less, and even more preferably 80.0% or less.

[0051] In this embodiment, the internal quantum efficiency of the phosphor powder when excited by light with a wavelength of 455 nm can be calculated, for example, based on the calculation results of the number of reflected excited light photons (Qref), the number of fluorescent photons (Qem), and the number of excited light photons (Qex) described above, based on the calculation formula shown below. Internal quantum efficiency = (Qem / (Qex-Qref)) x 100

[0052] (External quantum efficiency) The external quantum efficiency of the phosphor powder of this embodiment when excited by light with a wavelength of 455 nm is, from the viewpoint of further improving the performance balance of the reliability and fluorescent properties of the phosphor powder, preferably 60.0% or more, more preferably 63.0% or more, even more preferably 66.0% or more, even more preferably 68.0% or more, and preferably 99.0% or less, more preferably 90.0% or less, even more preferably 85.0% or less, and even more preferably 80.0% or less.

[0053] In this embodiment, the external quantum efficiency of the phosphor powder when excited by light with a wavelength of 455 nm can be calculated, for example, based on the calculation results of the number of reflected excited light photons (Qref), the number of fluorescent photons (Qem), and the number of excited light photons (Qex) described above, based on the calculation formula shown below. External quantum efficiency = (Qem / Qex) x 100 From the above formula, the relationship between the external quantum efficiency, the absorptance for 455 nm light, and the internal quantum efficiency can be expressed as follows: External quantum efficiency = absorptivity for 455 nm light × internal quantum efficiency

[0054] (Peak wavelength, half width) The peak wavelength of the fluorescence spectrum when the phosphor powder of this embodiment is irradiated with light having a wavelength of 455 nm is, from the viewpoint of further improving the performance balance of the reliability and fluorescence properties of the phosphor powder, preferably 600 nm or more, more preferably 610 nm or more, even more preferably 620 nm or more, even more preferably 630 nm or more, even more preferably 633 nm or more, and preferably 670 nm or less, more preferably 660 nm or less, even more preferably 650 nm or less, even more preferably 645 nm or less, and even more preferably 643 nm or less. Furthermore, from the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescent properties, the half-width of the peak of this fluorescent spectrum is preferably 70.0 nm or more, more preferably 71.0 nm or more, even more preferably 72.0 nm or more, even more preferably 73.0 nm or more, and is preferably 77.0 nm or less, more preferably 76.0 nm or less, even more preferably 75.0 nm or less. In this embodiment, the fluorescence spectrum when the phosphor powder is irradiated with light having a wavelength of 455 nm can be measured, for example, by a method similar to the method for measuring the absorptance Z1 described above.

[0055] (Relative Fluorescence Intensity) From the viewpoint of further improving the performance balance of the reliability and the fluorescent properties of the phosphor powder, the relative fluorescence intensity Y1 of the phosphor powder of this embodiment is preferably 150% or more, more preferably 170% or more, even more preferably 190% or more, even more preferably 200% or more, even more preferably 210% or more, even more preferably 220% or more, and even more preferably 225% or more. The upper limit of the relative fluorescence intensity Y1 is not particularly limited, and may be, for example, 400% or less, 350% or less, 300% or less, 280% or less, or 260% or less.

[0056] In this embodiment, the relative fluorescence intensity Y1 of the phosphor powder can be calculated by taking the peak intensity of the emission spectrum obtained by irradiating YAG:Ce with monochromatic light of 455 nm as 100% and expressing the peak intensity in the fluorescence spectrum measured by the same method as the above-mentioned method for measuring the absorptance Z1 as the relative peak intensity (%). In other words, the relative fluorescence intensity Y1 is a relative value to the standard sample.

[0057] (Absorption rate after pressure cooker test) Using a pressure cooker tester, 5 g of the phosphor powder of this embodiment is held for 53 hours under an atmosphere of 130°C, 98% relative humidity, and 0.16 MPaG. From the viewpoint of further improving the reliability of the phosphor powder, the absorptance Z2 of the phosphor powder of this embodiment for light with a wavelength of 455 nm is preferably 92.0% or more, more preferably 93.0% or more, even more preferably 94.0% or more, even more preferably 94.5% or more, and preferably 99.9% or less, more preferably 99.0% or less, even more preferably 98.5% or less. In this embodiment, the absorptance Z2 of the phosphor powder with respect to light having a wavelength of 455 nm can be determined, for example, by a method similar to the method for measuring the absorptance Z1 described above.

[0058] From the viewpoint of further improving the reliability of the phosphor powder, the absorptance reduction rate (%) of the phosphor powder of this embodiment, calculated by 100 × (Z1-Z2) / Z1, is preferably -5.0% or more, more preferably -1.0% or more, even more preferably 0.0% or more, and is preferably 5.0% or less, more preferably 4.0% or less, even more preferably 3.0% or less, even more preferably 2.5% or less, even more preferably 2.0% or less.

[0059] (Relative fluorescence intensity after pressure cooker test) The relative fluorescence intensity Y2 of the phosphor powder of this embodiment after 5 g of the phosphor powder of this embodiment is kept for 53 hours at 130°C, 98% relative humidity, and 0.16 MPaG using a pressure cooker tester, in terms of further improving the reliability of the phosphor powder, is preferably 221% or more, more preferably 223% or more, even more preferably 225% or more, and is preferably 400% or less, more preferably 300% or less, and even more preferably 260% or less. Furthermore, when the phosphor powder of this embodiment contains CASN phosphor particles, from the viewpoint of further improving the reliability of the phosphor powder, the relative fluorescence intensity Y2 is preferably 130% or more, more preferably 150% or more, even more preferably 170% or more, even more preferably 190% or more, even more preferably 200% or more, even more preferably 210% or more, even more preferably 220% or more, and is preferably 400% or less, more preferably 300% or less, even more preferably 260% or less.

[0060] From the viewpoint of further improving the reliability of the phosphor powder, the relative fluorescence intensity reduction rate (%) of the phosphor powder of this embodiment, calculated by 100 × (Y1-Y2) / Y1, is preferably -5.0% or more, more preferably -1.0% or more, even more preferably 0.0% or more, and is preferably 10.0% or less, more preferably 8.0% or less, even more preferably 6.0% or less, even more preferably 5.0% or less.

[0061] <Method of manufacturing phosphor powder> The phosphor powder of this embodiment can be obtained by appropriately selecting raw materials, the ratio of each raw material, the manufacturing procedure, the manufacturing conditions, etc. Specifically, the phosphor powder of this embodiment is preferably A mixing step of mixing the starting materials to obtain a raw material mixture powder; A sintering process for sintering the raw material powder mixture to obtain a lump of sintered powder; A powdering process for powdering the lump-shaped fired powder; An annealing process in which the powdered fired powder is heat-treated to obtain annealed powder; an acid treatment step of treating the annealed powder with an acid to obtain an acid-treated powder; - An elutriation process for removing fine particles from the acid-treated powder by elutriation; an atmospheric heat treatment step of atmospherically heat treating the acid-treated powder to obtain atmospherically heat-treated powder; The phosphor powder can be produced through the steps. In addition, the phosphor powder may be produced through additional steps other than those described above.

[0062] (Mixing process) In the mixing step of the present embodiment, starting materials are mixed to obtain a raw material mixed powder. From the viewpoint of further improving the fluorescence characteristics of the phosphor powder, the starting materials of the present embodiment preferably all include a europium compound, a strontium compound, a calcium compound, silicon nitride, and aluminum nitride, and more preferably all include europium oxide, strontium nitride, calcium nitride, silicon nitride, and aluminum nitride. The form of each starting material of the present embodiment is preferably powdery.

[0063] From the viewpoint of further improving the fluorescence characteristics of the phosphor powder, the europium compound of the present embodiment preferably contains, alone, one selected from the group consisting of europium oxide, europium nitride, and europium fluoride, and more preferably contains europium oxide alone.

[0064] In the firing step of the present embodiment, europium is divided into those that dissolve, those that volatilize, and those that remain as heterogeneous components. The heterogeneous components containing europium can be removed by acid treatment or the like. However, when too much heterogeneous components containing europium are generated, components insoluble in acid treatment are generated and the luminance decreases. Also, if it is a heterogeneous phase that does not absorb excess light, it may remain as it is, and europium may be contained in this heterogeneous phase.

[0065] From the viewpoint of further improving the fluorescence characteristics of the phosphor powder, the amount of the europium compound of the present embodiment is preferably used in such an amount that 0.05 < a < 0.15, more preferably 0.07 < a < 0.10, in the above general formula in the charging ratio. Incidentally, when using the core particles described later, the amount of europium in the core particles is not included in a in the above inequality.

[0066] On the one hand, from the perspective of further improving the fluorescence characteristics of the phosphor powder, the amount of the strontium compound in this embodiment is preferably used in an amount such that b in the above general formula in the charging ratio is preferably 0.85 < b < 1.00, more preferably 0.95 < b < 0.98. Incidentally, when using the core particles described later, the amount of strontium in the core particles is not included in b in the above inequality.

[0067] The starting material of this embodiment (the raw material mixed powder) preferably contains SCASN phosphor core particles having a median diameter of 10 μm or more and 20 μm or less. That is, a part of the starting material is preferably SCASN phosphor core particles having a median diameter of 10 μm or more and 20 μm or less. From the perspective of further improving the fluorescence characteristics of the phosphor powder, the median diameter of the SCASN phosphor core particles in this embodiment is preferably 10 μm or more, more preferably 15 μm or more, and preferably 20 μm or less, more preferably 17 μm or less. In this specification, this SCASN phosphor core particle is also simply referred to as "core particle", "core", etc.

[0068] Although the details are unknown, it is considered that by using the core particles, crystallization proceeds starting from the core particles in the subsequent firing process. For this reason, it is considered that the way of crystal growth changes compared with the case of performing the firing process without using the core particles (for example, by using the core, the composition of each particle is considered to be easier to be uniform compared with the case of not using the core). And probably as a result, it is considered that it becomes easier to obtain a phosphor powder with improved fluorescence characteristics.

[0069] As an example, the core particles of this embodiment can be a phosphor powder represented by the same general formula as the phosphor powder of this embodiment described above. In other words, as an example, in the infrared absorption spectrum of the Kubelka-Munk function value (KM value) by FT-IR measurement, the core particles have an absorption peak a in the wavenumber region of 3200 cm -1 or more and 3350 cm -1 less than, and the KM value of the absorption peak a does not necessarily have to be 1.25 or less, but has the same or similar composition as the phosphor powder of this embodiment.

[0070] When core particles are used, the amount thereof is preferably 7 mass % or more, more preferably 9 mass % or more, and preferably 13 mass % or less, more preferably 11 mass % or less, of the total amount of the raw material mixed powder, from the viewpoint of further improving the fluorescent properties of the phosphor powder.

[0071] The core particles can be obtained, for example, through a process almost similar to that of the phosphor powder of this embodiment. That is, in the manufacturing process of the phosphor powder of this embodiment, the core particles can be obtained in the same manner except that the core particles are not added in the mixing process. The composition (general formula) of the core particles is also preferably the same as that of the phosphor powder of this embodiment.

[0072] In the mixing step of this embodiment, the raw material mixed powder can be obtained, for example, by a method of dry mixing the starting materials, or a method of wet mixing in an inert solvent that does not substantially react with each starting material and then removing the solvent. As a mixing device, for example, a small mill mixer, a V-type mixer, a rocking mixer, a ball mill, a vibration mill, etc. can be used. After mixing using the device, the raw material mixed powder can be obtained by removing aggregates using a sieve as necessary. In order to prevent deterioration of the starting materials and unintended inclusion of oxygen, the mixing step of this embodiment is preferably carried out in a nitrogen atmosphere or in an environment with as little moisture (humidity) as possible.

[0073] (Firing process) In the firing step of this embodiment, the raw material mixed powder obtained in the mixing step is fired to obtain a fired powder. The firing temperature in the firing step of this embodiment is preferably 1850°C or higher, more preferably 1900°C or higher, and preferably 2050°C or lower, more preferably 2000°C or lower, from the viewpoint of further improving the performance balance of the reliability and fluorescent properties of the phosphor powder. When the firing temperature is equal to or higher than the lower limit, the grain growth of the phosphor particles proceeds more effectively. Therefore, the reliability and the performance balance of the fluorescent properties of the phosphor powder can be further improved. When the firing temperature is equal to or lower than the upper limit, the decomposition of the phosphor particles can be further suppressed. Therefore, the reliability and the performance balance of the fluorescent properties of the phosphor powder can be further improved.

[0074] The heating and holding time in the firing process of this embodiment is preferably 5 hours or more, more preferably 7 hours or more, and preferably 15 hours or less, and even more preferably 10 hours or less, from the viewpoint of further improving the performance balance of the reliability and fluorescent properties of the phosphor powder. The pressure in the firing process of this embodiment is preferably 0.7 MPaG or more, more preferably 0.8 MPaG or more, and preferably 1 MPaG or less, more preferably 0.9 MPaG or less, from the viewpoint of further improving the performance balance of the reliability and fluorescent properties of the phosphor powder. From the viewpoint of controlling the oxygen concentration, the firing step of this embodiment is preferably performed in a nitrogen gas atmosphere, that is, in a nitrogen gas atmosphere with a pressure of 0.7 MPaG or more and 1 MPaG or less.

[0075] In the firing step of this embodiment, in order to further improve the reliability of the phosphor powder and the performance balance of the fluorescent properties, it is preferable to fill the mixture in a container that is unlikely to react with the raw material mixed powder during firing and heat it. Specifically, it is preferable to use a high melting point container, and more preferably a tungsten container. This makes it possible to suppress the generation of heterogeneous phases.

[0076] In addition, in the firing step of this embodiment, from the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescent properties, it is preferable that the container is a sealed container with high airtightness. By firing the raw material mixed powder under sealed conditions, it is possible to prevent the intrusion of oxygen and moisture (humidity) into the container and suppress deterioration of the raw material mixed powder, thereby further improving the reliability of the phosphor powder and the performance balance of the fluorescent properties. The structure of the sealed container is preferably such that the inside of the container is sealed by narrowing the gap between the lid and the body of the container. As a method for narrowing the gap between the lid and the body of the sealed container, for example, a method of making the body and the lid of the container fit together, whereas a conventional container has a structure in which the lid is simply placed on the body, can be mentioned.

[0077] (Powderization process) In the pulverization step of this embodiment, the sintered powder is once pulverized by using a single or a combination of processes such as crushing, grinding, and classification. Since the sintered powder obtained through the sintering step is usually a sintered block, the sintered powder is pulverized to make it easier to handle.

[0078] A specific processing method for the powdering step of this embodiment is, for example, a method of pulverizing the sintered body to a predetermined particle size using a general pulverizer such as a ball mill, a vibration mill, a jet mill, etc. However, care should be taken because excessive pulverization may generate fine particles that easily scatter light or may cause crystal defects on the particle surface, resulting in a decrease in luminous efficiency.

[0079] (Annealing process) In the annealing step of the present embodiment, after the pulverization step, the sintered powder is annealed at a temperature lower than the sintering temperature in the sintering step to obtain an annealed powder. This can sufficiently improve the luminous efficiency of the phosphor powder, and also can improve the reliability of the phosphor powder and the performance balance of the fluorescent properties, since the rearrangement of the elements removes distortions and defects. On the other hand, the annealing step may result in the generation of heterogeneous phases, but these can be sufficiently removed by the acid treatment step described below.

[0080] From the viewpoint of further improving the performance balance between the reliability and the fluorescent properties of the phosphor powder, the annealing step of this embodiment is preferably carried out in a hydrogen gas atmosphere or an argon atmosphere, and more preferably in an argon atmosphere.

[0081] The pressure in the annealing process of this embodiment is preferably 0.7 MPaG or more, more preferably 0.8 MPaG or more, and preferably 1 MPaG or less, more preferably 0.9 MPaG or less, from the viewpoint of further improving the performance balance of the reliability and fluorescent properties of the phosphor powder. The heat treatment temperature in the annealing step of this embodiment is preferably 1250°C or higher, more preferably 1300°C or higher, and preferably 1450°C or lower, more preferably 1400°C or lower, from the viewpoint of further improving the performance balance of the reliability and fluorescent properties of the phosphor powder. The heat treatment time in the annealing step of this embodiment is preferably 5 hours or more, more preferably 7 hours or more, and preferably 10 hours or less, and even more preferably 9 hours or less, from the viewpoint of further improving the performance balance of the reliability and fluorescent properties of the phosphor powder.

[0082] In the annealing step of this embodiment, similarly to the sintering step, it is preferable to fill the mixture in a container that is unlikely to react with the sintered powder during heat treatment, for example, a high-melting-point container, specifically a container whose inner wall is made of tungsten, and heat it. In addition, from the viewpoint of further improving the performance balance of the reliability and fluorescent properties of the phosphor powder, it is preferable that the container used in the annealing process is a sealed container as described above, and it is even more preferable that both the containers used in the firing process and the annealing process are sealed containers.

[0083] (Acid treatment process) In the acid treatment step of the present embodiment, the annealed powder obtained in the annealing step is subjected to an acid treatment to obtain an acid-treated powder. This makes it possible to remove at least a portion of the impurities that do not contribute to light emission. Incidentally, it is presumed that the impurities that do not contribute to light emission are generated during the firing and annealing steps.

[0084] In the acid treatment step of this embodiment, an aqueous solution containing one or more acids selected from the group consisting of hydrofluoric acid, sulfuric acid, phosphoric acid, hydrochloric acid, and nitric acid can be used as the acid. In particular, from the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescent properties, the aqueous solution preferably contains hydrochloric acid, hydrofluoric acid, nitric acid, or a mixed acid of hydrofluoric acid and nitric acid, and more preferably contains hydrochloric acid.

[0085] The acid treatment step of this embodiment can be performed by dispersing the annealed powder in an aqueous solution containing the above-mentioned acid. From the viewpoint of further improving the performance balance of the reliability and the fluorescent properties of the phosphor powder, the stirring time is preferably 30 minutes or more, more preferably 45 minutes or more, and preferably 3 hours or less, more preferably 2 hours or less. In addition, from the viewpoint of further improving the performance balance of the reliability and the fluorescent properties of the phosphor powder, the stirring temperature is preferably 50°C or more, more preferably 60°C or more, and preferably 100°C or less, more preferably 90°C or less.

[0086] After the acid treatment step of this embodiment, the liquid in which the annealed powder is dispersed may be boiled, and substances other than the phosphor powder may be separated by filtration, and substances attached to the phosphor particles may be washed with water as necessary. After washing with water, the phosphor powder is usually dried by natural drying or drying in a dryer. The dried phosphor powder may be placed in a crucible and heated to modify the surface.

[0087] (Elutriation process) In the elutriation step of this embodiment, after the acid treatment step, fine particles are removed from the acid-treated powder by elutriation. This makes it possible to remove fine particles that may deteriorate the fluorescent properties of the phosphor powder, and to further improve the reliability of the phosphor powder and the performance balance of the fluorescent properties.

[0088] The elutriation process is carried out by putting the acid-treated powder into a dispersion medium, preparing a dispersion liquid, stirring the mixture, precipitating the acid-treated powder in the dispersion liquid, and removing the supernatant. After removing the supernatant, the precipitate is collected by filtration and dried to obtain an acid-treated powder from which the fine particle powder has been removed. In the elutriation process, the above-mentioned preparation of the dispersion liquid and removal of the supernatant may be repeated. As the dispersion medium, it is preferable to use an aqueous solution of sodium hexametaphosphate from the viewpoint of further improving the performance balance of the reliability and fluorescent properties of the phosphor powder.

[0089] (Atmospheric heat treatment process) In the atmospheric heat treatment step of this embodiment, after the elutriation step, the acid-treated powder is subjected to atmospheric heat treatment to obtain atmospheric heat-treated powder. This improves the reliability of the phosphor powder and the balance of its fluorescent properties. However, since excessive atmospheric heat treatment reduces the fluorescent properties of the phosphor powder, it is important to perform atmospheric heat treatment under appropriate conditions in order to improve the reliability of the phosphor powder and the balance of its fluorescent properties.

[0090] The atmospheric heat treatment step of the present embodiment is preferably carried out in the atmosphere under atmospheric pressure, from the viewpoint of further improving the performance balance of the reliability and the fluorescent properties of the phosphor powder. From the viewpoint of further improving the performance balance between the reliability and the fluorescent properties of the phosphor powder, the heat treatment temperature in the atmospheric heat treatment step of this embodiment is preferably 250° C. or higher, more preferably 280° C. or higher, even more preferably 320° C. or higher, even more preferably 350° C. or higher, even more preferably 380° C. or higher, and preferably 450° C. or lower, more preferably 420° C. or lower. By setting the heat treatment temperature to be equal to or higher than the lower limit, the reliability of the phosphor powder can be further improved, and by setting the heat treatment temperature to be equal to or lower than the upper limit, the deterioration of the fluorescent properties of the phosphor powder can be suppressed.

[0091] From the viewpoint of further improving the performance balance between the reliability and the fluorescent properties of the phosphor powder, the heat treatment time in the atmospheric heat treatment step of this embodiment is preferably 0.5 hours or more, more preferably 2 hours or more, even more preferably 3.5 hours or more, and preferably 6 hours or less, even more preferably 5 hours or less. By setting the heat treatment time to the lower limit or more, the reliability of the phosphor powder can be further improved, and by setting the heat treatment time to the upper limit or less, the deterioration of the fluorescent properties of the phosphor powder can be suppressed.

[0092] The heating rate in the atmospheric heating treatment process of this embodiment is preferably 1°C / min or more, more preferably 2°C / min or more, and preferably 10°C / min or less, more preferably 5°C / min or less, and even more preferably 3°C / min or less, from the viewpoint of further improving the performance balance of the reliability and fluorescent properties of the phosphor powder.

[0093] <Complex> The composite of the present embodiment includes, for example, the above-described phosphor powder and a sealant that seals the phosphor powder. In the composite of the present embodiment, the above-described phosphor powder is dispersed in the sealant. From the viewpoint of further improving the reliability of the composite, the sealing material of the present embodiment preferably contains one or more materials selected from the group consisting of silicone resin, epoxy resin, urethane resin, glass, and ceramics.

[0094] The content of the phosphor powder in this embodiment, when the total amount of the composite is taken as 100 mass%, is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, even more preferably 1 mass% or more, from the viewpoint of further improving the reliability of the composite, and is preferably 20 mass% or less, more preferably 15 mass% or less, even more preferably 10 mass% or less, even more preferably 5 mass% or less.

[0095] The composite of this embodiment can be produced by adding the phosphor powder of this embodiment to liquid resin, glass, ceramics, etc., mixing them uniformly, and then curing or sintering them by heat treatment.

[0096] <Light emitting device> The light emitting device of the present embodiment includes a light emitting element that emits excitation light, and the composite of the present embodiment that converts the wavelength of the excitation light. The light emitting device of this embodiment will be described below with reference to Fig. 1, which is a schematic cross-sectional view showing an example of the structure of the light emitting device of this embodiment. As shown in Fig. 1, the light emitting device 100 includes a light emitting element 120, a heat sink 130, a case 140, a first lead frame 150, a second lead frame 160, a bonding wire 170, a bonding wire 172, and a composite body 40.

[0097] The light emitting element 120 is mounted in a predetermined region on the upper surface of the heat sink 130. By mounting the light emitting element 120 on the heat sink 130, it is possible to improve the heat dissipation properties of the light emitting element 120. Note that a packaging substrate may be used instead of the heat sink 130.

[0098] The light emitting element 120 is a semiconductor element that emits excitation light. For example, an LED chip that emits light with a wavelength of 300 nm to 500 nm, which corresponds to near ultraviolet to blue light, can be used as the light emitting element 120. One electrode (not shown) disposed on the upper surface side of the light emitting element 120 is connected to the surface of the first lead frame 150 via a bonding wire 170 such as a gold wire. The other electrode (not shown) formed on the upper surface of the light emitting element 120 is connected to the surface of the second lead frame 160 via a bonding wire 172 such as a gold wire.

[0099] A generally funnel-shaped recess whose hole diameter gradually increases from the bottom surface toward the top is formed in the case 140. The light emitting element 120 is provided on the bottom surface of the recess. The wall surface of the recess surrounding the light emitting element 120 serves as a reflector.

[0100] The composite 40 is filled in the recess whose wall is formed by the case 140. The composite 40 is a wavelength conversion member that converts the excitation light emitted from the light emitting element 120 into light with a longer wavelength. The composite of this embodiment is used as the composite 40, and the above-mentioned phosphor powder 1 is dispersed in the sealing material 30 such as a resin. The light emitting device 100 emits a mixed color of the light of the light emitting element 120 and the light generated from the phosphor powder 1 that is excited by absorbing the light of the light emitting element 120. In order to obtain white as the mixed color (to make the light emitting device 100 a white LED), it is preferable that the composite 40 contains, for example, LuAG phosphor powder in addition to the phosphor powder 1 (it is preferable that LuAG phosphor powder is dispersed in the sealing material 30 in addition to the phosphor powder 1). In this embodiment, since the peak wavelength and the half width of the fluorescence spectrum of the phosphor powder 1 are within certain numerical ranges, good white light can be easily obtained.

[0101] 1 shows a surface-mounted light-emitting device, but the light-emitting device is not limited to the surface-mounted type. The light-emitting device may be a bullet type, a COB (chip-on-board) type, a CSP (chip-scale package) type, or the like.

[0102] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES

[0103] The embodiments of the present invention will be described in detail based on examples and comparative examples. However, the present invention is not limited to the examples.

[0104] Example 1 <Preparation of nucleating agent> First, 60.61 g of α-type silicon nitride (Si3N4, manufactured by Ube Industries, Ltd., SN-E10 grade), 53.13 g of aluminum nitride (AlN, manufactured by Tokuyama Corporation, E grade), and 13.68 g of europium oxide (Eu2O3, manufactured by Shin-Etsu Chemical Co., Ltd.) were placed in a container and premixed.

[0105] Next, in a glove box maintained in a nitrogen atmosphere with a moisture content of 1 mass ppm or less and an oxygen concentration of 50 mass ppm or less, 5.76 g of calcium nitride (Ca3N2, manufactured by Materion) and 106.82 g of strontium nitride (Sr3N2, manufactured by Kojundo Chemical Laboratory Co., Ltd., purity 2N) were further added to the above container and dry-mixed to obtain a mixture.

[0106] In a glove box, 240 g of the mixture was filled into a sealed container made of tungsten. After closing the lid of the sealed container, it was removed from the glove box and placed in an electric furnace equipped with a carbon heater. Then, the electric furnace was fully evacuated until the pressure inside the furnace was 0.1 PaG or less. Here, the sealed container has a structure in which the main body and the lid are fitted together, so that the gap between the lid and the main body is narrower than that of conventional containers, and the sealing performance is improved.

[0107] While continuing the vacuum evacuation, the temperature in the electric furnace was raised to 600°C. After reaching 600°C, nitrogen gas was introduced into the electric furnace, and the pressure in the electric furnace was adjusted to 0.85MPaG. Then, in a nitrogen gas atmosphere, the temperature in the electric furnace was raised to 1950°C, and after reaching 1950°C, heat treatment was carried out for 8 hours. Then, heating was terminated and the material was cooled to room temperature. After cooling to room temperature, red lumps were collected from the container. The collected lumps were crushed and sieved in a mortar to prepare core particles (nucleating agent) with a median diameter of 16 μm.

[0108] <Production of phosphor powder> Into a container, 51.50 g of α-type silicon nitride (Si3N4, Ube Industries, SN-E10 grade), 45.14 g of aluminum nitride (AlN, Tokuyama Corporation, E grade), 15.50 g of europium oxide (Eu2O3, Shin-Etsu Chemical Co., Ltd.), and 24.00 g of the nucleating agent prepared as described above were weighed and premixed.

[0109] Next, in a glove box maintained in a nitrogen atmosphere with a moisture content of 1 mass ppm or less and an oxygen concentration of 50 mass ppm or less, 0.27 g of calcium nitride (Ca3N2, manufactured by Materion) and 103.58 g of strontium nitride (Sr3N2, manufactured by Kojundo Chemical Laboratory Co., Ltd., purity 2N) were further weighed and dry mixed into the above container. A mixed powder was obtained in this way. The relationship between the amount of the nucleating agent and the raw material powder charged (mass %) and the breakdown of the amount of each element charged in the raw material powder (molar ratio) are shown in Table 1.

[0110] In a glove box, 240 g of the mixed powder was filled into a sealed container made of tungsten. After closing the lid of the sealed container, it was removed from the glove box and placed in an electric furnace equipped with a carbon heater. Then, the electric furnace was evacuated sufficiently until the pressure inside the electric furnace became 0.1 PaG or less.

[0111] While continuing the vacuum evacuation, the temperature in the electric furnace was raised to 600°C. After reaching 600°C, nitrogen gas was introduced into the electric furnace, and the pressure in the electric furnace was adjusted to 0.85MPaG. Then, under a nitrogen gas atmosphere, the temperature in the electric furnace was raised to 1950°C, and after reaching 1950°C, heat treatment was performed for 8 hours. Then, heating was terminated and the material was cooled to room temperature. After cooling to room temperature, red lumps were collected from the container. The collected lumps were crushed and sieved to adjust the particle size to obtain a fired powder.

[0112] The obtained sintered powder was filled into a sealed container made of tungsten, and quickly transferred to an electric furnace equipped with a carbon heater, and the pressure in the furnace was sufficiently evacuated until it reached 0.1 PaG or less. Heating was started while continuing the evacuation, and when the temperature reached 600 ° C, argon gas was introduced into the furnace, and the pressure of the atmosphere in the furnace was adjusted to atmospheric pressure. The temperature continued to be raised to 1350 ° C even after the introduction of argon gas was started. After the temperature reached 1350 ° C, the heat treatment was performed for 8 hours. After that, the heating was stopped and the mixture was cooled to room temperature. After cooling to room temperature, the powder after the annealing treatment was collected from the container. The collected powder was passed through a sieve to adjust the particle size. In this way, the annealed powder was obtained.

[0113] The obtained annealed powder was put into 2.0M hydrochloric acid at room temperature so that the slurry concentration was 25 mass%, and immersed for 1 hour under conditions of 70 to 80°C. In this way, an acid treatment was performed. After the acid treatment, the hydrochloric acid slurry was boiled for 1 hour while stirring. The slurry after the boiling treatment was cooled to room temperature and filtered to separate the acid treatment liquid from the solid content, and an acid treatment product was obtained. The acid treatment product was placed in a dryer set at a temperature in the range of 100 to 120°C for 12 hours and dried, and an acid treatment powder was obtained.

[0114] The obtained acid-treated powder was put into an aqueous solution of sodium hexametaphosphate to prepare a dispersion liquid, which was then stirred. The acid-treated powder in the dispersion liquid was then precipitated, and the supernatant was removed. After removing the supernatant, the precipitate was collected by filtration and dried to obtain an acid-treated powder from which fine particles had been removed. The preparation of the dispersion liquid and the removal of the supernatant were repeated five times.

[0115] The obtained acid-treated powder was then filled into an alumina crucible and quickly transferred to an electric furnace equipped with a carbon heater, where it was heated at a rate of 2.5°C / min under atmospheric pressure and in an air atmosphere until the temperature reached 300°C. After the temperature reached 300°C, air heat treatment was carried out for 1 hour. After that, the heating was terminated and the powder was cooled to room temperature to obtain air heat-treated powder. In this manner, the phosphor powder of Example 1 was obtained.

[0116] The obtained phosphor sample was subjected to powder X-ray diffraction using CuKα radiation using an X-ray diffractometer (Ultima IV manufactured by Rigaku Corporation). The obtained X-ray diffraction pattern was identical to that of CaAlSiN3 crystals, and it was confirmed that the main crystal phase had the same crystal structure as CaAlSiN3 crystals.

[0117] Example 2 A phosphor powder of Example 2 was obtained in the same manner as in Example 1, except that the atmospheric heat treatment was performed at a temperature of 400°C.

[0118] Example 3 A phosphor powder of Example 3 was obtained in the same manner as in Example 1, except that the heat treatment in air was carried out for 4 hours.

[0119] Example 4 A phosphor powder of Example 4 was obtained in the same manner as in Example 1, except that the atmospheric heat treatment was performed at a treatment temperature of 400° C. for a treatment time of 4 hours.

[0120] Comparative Example 1 A phosphor powder of Comparative Example 1 was obtained in the same manner as in Example 1, except that the heat treatment in air was not carried out.

[0121] Comparative Example 2 A phosphor powder of Comparative Example 2 was obtained in the same manner as in Example 1, except that the atmospheric heat treatment was performed at a temperature of 200°C.

[0122] Comparative Example 3 A phosphor powder of Comparative Example 3 was obtained in the same manner as in Example 1, except that a non-sealed tungsten container was used instead of a sealed tungsten container for firing and annealing. Here, the non-sealed container is a container having a structure in which a lid is simply placed on a main body.

[0123] <Infrared absorption spectrum, KM value> First, about 50 mg of phosphor powder was weighed out and filled into a measuring cup without dilution. The infrared absorption spectrum of the Kubelka-Munk function value (KM value) was measured by the diffuse reflection method using a Fourier transform infrared spectrometer (Spectrum One, manufactured by PerkinElmer). Next, based on the obtained infrared absorption spectrum, -1 More than 3350cm -1 The KM value A of the absorption peak a in the wavenumber range below 3350 cm -1 More than 3450cm -1 The KM value B of the absorption peak b present in the following wave number region was determined. The results are shown in Table 2.

[0124] <Water content> First, the mass (mg) of water generated from the phosphor powder when heated to 400°C under a nitrogen gas flow rate of 300mL / min was measured by coulometric titration in accordance with JIS K 0068:2001 using a Karl Fischer moisture analyzer (Mitsubishi Chemical, CA-100) and a moisture vaporizer (Mitsubishi Chemical, VA-22). In the measurement, Aquamicron AX (Mitsubishi Chemical) was used as the anolyte, and Aquamicron CXU (Mitsubishi Chemical) was used as the catholyte. Next, the water content was calculated when the total amount of the phosphor powder was taken as 100% by mass, and this was taken as the moisture content (% by mass). The results are shown in Table 2.

[0125] <Oxygen increase rate> The oxygen content X1 (mass%) of the phosphor powder was obtained by weighing out 0.03 g of the phosphor powder and measuring the oxygen content with an oxygen / nitrogen analyzer (EMGA-920, manufactured by Horiba, Ltd.). Next, using a pressure cooker tester (EHS-221M, manufactured by Espec Corp.), 5 g of the phosphor powder was held at 130°C, 98% relative humidity, and 0.16 MPaG for 53 hours, and then the oxygen content X2 (mass%) of the phosphor powder was measured in the same manner as X1. From the above measured values, the increase rate (%) of the oxygen content of the phosphor powder before and after the pressure cooker test was calculated by 100×X2 / X1. The results are shown in Table 2.

[0126] <Color difference ΔE * > First, using a color difference meter (ZE6000, manufactured by Nippon Denshoku Industries Co., Ltd.), the CIE1976L color difference of the phosphor powder was measured under the conditions of C light source and 2° field of view. * a * b * Chromaticity coordinates (L1 * , a1 * , b1 * Next, a pressure cooker test was performed using a pressure cooker tester (EHS-221M, manufactured by Espec Corp.) in which 5 g of the phosphor powder was exposed to an atmosphere of 130°C, 98% relative humidity, and 0.16 MPa for 53 hours. The CIE1976L * a * b * Chromaticity coordinates (L2 * , a2 * , b2 * ) was measured in the same manner. Next, based on the measured values ​​of each chromaticity coordinate, (L1 * -L2 * ) 2 , (a1 * -a2 * ) 2 and (b1 * -b2 * ) 2 Then, ΔE was calculated using the following formula: * The results are shown in Table 2. ΔE * ={(L1 * -L2 * ) 2 +(a1 * -a2 * ) 2 +(b1 * -b2 * ) 2} 1 / 2

[0127] <Composition> First, the phosphor powder was dissolved by the pressurized acid decomposition method to prepare a sample solution. Next, the obtained sample solution was subjected to quantitative element analysis using an ICP emission spectrometer (Shimadzu Corporation, ICPE-9000) to measure the molar ratios of Eu, Sr, Ca, Al, and Si contained in the phosphor powder. The results are shown in Table 1. Furthermore, 0.03 g of the phosphor powder was weighed out, and the oxygen and nitrogen contents were measured using an oxygen / nitrogen analyzer to determine the molar ratio of N and O. The results are shown in Table 1.

[0128] <Median diameter> The particle size distribution of the phosphor powder was measured using a Microtrac MT3300EX II (manufactured by Microtrac Bell) by the laser diffraction scattering method in accordance with JIS R1629:1997. Specifically, about 0.1 g of phosphor powder was put into 100 mL of ion-exchanged water, and a dispersion process was performed for 3 minutes using an Ultrasonic Homogenizer US-150E (manufactured by Nippon Seiki Seisakusho, tip size φ20 mm, Amplitude 100%, oscillation frequency 19.5 KHz, amplitude approximately 31 μm), and then measurement was performed using the MT3300EX II. From the obtained particle size distribution, the median diameter D 50 The results are shown in Table 2.

[0129] <Fluorescence spectrum> Fluorescence measurements were performed using a spectrofluorophotometer (Hitachi High-Technologies Corporation, F-7000) with correction using Rhodamine B and a secondary standard light source. Specifically, the phosphor powder was first filled into a concave cell so that the surface was smooth, and the cell was attached to the opening of an integrating sphere. Next, monochromatic light with a wavelength of 455 nm was split from a Xe lamp, which is a light source, and introduced into the integrating sphere using an optical fiber as excitation light for the phosphor. The phosphor powder was irradiated with the monochromatic light, which was the excitation light, and the fluorescence spectrum was measured using a spectrophotometer.

[0130] <Peak wavelength, half-width, relative fluorescence intensity> The obtained phosphor powder was irradiated with light having a wavelength of 455 nm, and the peak wavelength and half-width of the peak were obtained from the fluorescence spectrum. The relative fluorescence intensity Y1 of the phosphor powder was also obtained from the peak intensity. The results are shown in Table 2. Here, the relative fluorescence intensity Y1 was calculated by taking the peak height of the emission spectrum obtained by irradiating YAG:Ce (P46Y3, manufactured by Kasei Optonix Co., Ltd.) with monochromatic light of 455 nm as 100%, and expressing the peak intensity of the above fluorescence spectrum as the relative peak intensity (%). In other words, the relative fluorescence intensity Y1 is a relative value to the standard sample.

[0131] <Absorptivity, Internal Quantum Efficiency, External Quantum Efficiency> From the obtained fluorescence spectrum data, the emission intensity of the phosphor powder was determined, and the number of excitation reflected light photons (Qref) and the number of fluorescence photons (Qem) were calculated. The number of excitation reflected light photons was calculated in the wavelength range of 450 to 465 nm, and the number of fluorescence photons was calculated in the range of 465 to 800 nm. In addition, using the same device, a standard reflector with a reflectance of 99% (Spectralon (registered trademark) manufactured by Labsphere) was attached to the opening of the integrating sphere to measure the spectrum of excitation light with a wavelength of 455 nm. At that time, the number of excitation light photons (Qex) was calculated from the spectrum in the wavelength range of 450 to 465 nm. From the above calculation results, the absorptance Z1, internal quantum efficiency, and external quantum efficiency of the phosphor powder for light of 455 nm were calculated based on the following formula. The results are shown in Table 2. Absorption rate for 455 nm light Z1 = ((Qex-Qref) / Qex) x 100 Internal quantum efficiency = (Qem / (Qex-Qref)) x 100 External quantum efficiency = (Qem / Qex) x 100

[0132] <Relative fluorescence intensity decrease rate> Using a pressure cooker tester (EHS-221M, manufactured by Espec Corp.), 5 g of phosphor powder was held at 130°C, 98% relative humidity, and 0.16 MPaG for 53 hours, after which the relative fluorescence intensity Y2 (%) of the phosphor powder was measured in the same manner as for Y1 described above. From these measured values, the reduction rate (%) of the relative fluorescence intensity of the phosphor powder before and after the pressure cooker test was calculated by 100 x (Y1 - Y2) / Y1. The results are shown in Table 2.

[0133] <Absorption rate reduction rate> Using a pressure cooker tester (EHS-221M, manufactured by Espec Corp.), 5 g of phosphor powder was held at 130°C, 98% relative humidity, and 0.16 MPaG for 53 hours, after which the absorptivity Z2 (%) of the phosphor powder to light at 455 nm was measured in the same manner as Z1 described above. From these measured values, the absorptivity reduction rate (%) of the phosphor powder before and after the pressure cooker test was calculated by 100 x (Z1 - Z2) / Z1. The results are shown in Table 2.

[0134] The raw material ratios are shown in Table 1. In Table 1, the values ​​in the columns Eu (molar ratio), Sr (molar ratio), Ca (molar ratio), Al (molar ratio), Si (molar ratio), and b / (b+c) do not include the elements in the core particles.

[0135] [Table 1]

[0136] [Table 2]

[0137] The phosphor powders of Examples 1 to 4, in which the KM value A of the absorption peak a was 1.25 or less, had a relative fluorescence intensity decrease rate of 3.7% or less and an absorptivity decrease rate of 1.6% or less. On the other hand, the phosphor powders of Comparative Examples 1 to 3, in which the KM value A of the absorption peak a exceeded 1.25, had a relative fluorescence intensity decrease rate of 10.5% or more and an absorptivity decrease rate of 5.2% or more. From this, it can be seen that the phosphor powders of Examples 1-4 have improved reliability compared to the phosphor powders of Comparative Examples 1-3. [Explanation of symbols]

[0138] 1. Phosphor powder 30 Encapsulating material 40 Complex 100 Light emitting device 120 Light emitting element 130 Heat sink 140 cases 150 First lead frame 160 Second lead frame 170 Bonding Wire 172 Bonding Wire

Claims

1. A phosphor powder comprising one or more phosphor particles selected from the group consisting of CASN phosphor particles and SCASN phosphor particles, In the infrared absorption spectrum of the phosphor powder, the Kubelka-Munk function value (KM value) measured by FT-IR measurement is 3200 cm -1 More than 3350cm -1 has an absorption peak a in a wave number region less than The phosphor powder has a KM value of the absorption peak a of 1.25 or less.

2. In the infrared absorption spectrum of the Kubelka-Munk function value (KM value), -1 More than 3450cm -1 It further has an absorption peak b in the following wave number region:

2. The phosphor powder according to claim 1, wherein the KM value of the absorption peak b is 1.24 or less.

3. 3. The phosphor powder according to claim 2, wherein when the KM value of the absorption peak a is A and the KM value of the absorption peak b is B, A>B is satisfied.

4. 3. The phosphor powder according to claim 1, wherein the phosphor powder has a moisture content of 0.38% by mass or less, the moisture content being determined by the following method 1. (Method 1) Using a Karl Fischer moisture meter and a moisture vaporizer, the mass (mg) of water generated from the phosphor powder when heated to 400° C. under conditions of a nitrogen gas flow rate of 300 mL / min is measured by coulometric titration in accordance with JIS K 0068: 2001. Next, the water content is calculated when the total amount of the phosphor powder is taken as 100% by mass, and this is taken as the moisture amount (% by mass).

5. General formula, Eu a Sr b Ca c A d S e N f O g 3. The phosphor powder according to claim 1, comprising phosphor particles represented by the formula: 0<a<1.00, 0<b<1.00, 0<c<1.00, 0.70<a+b+c<1.30, 0.70<d<1.30, 0.70<e<1.30, 0<f<3.00, 0<g<3.00, and 2.50<f+g<3.

50.

6. The phosphor powder according to claim 5 , wherein a<0.

30.

7. The phosphor powder according to claim 5 , wherein b>0.

50.

8. The phosphor powder according to claim 5 , wherein the molar ratio b / (b+c) of the phosphor powder is 0.96 or more and 0.99 or less.

9. The volume-based median diameter D of the phosphor powder measured by the laser diffraction scattering method 50 The phosphor powder according to claim 1 or 2, wherein the particle size is 1 μm or more and 40 μm or less.

10. 3. The phosphor powder according to claim 1, wherein a relative fluorescence intensity reduction rate of the phosphor powder according to the following method 2 is 10.0% or less. (Method 2) The relative fluorescence intensity of the phosphor powder measured using a spectrophotometer is defined as Y 1 (%), and the relative fluorescence intensity of the phosphor powder after 5 g of the phosphor powder was kept for 53 hours under an atmosphere of 130° C., 98% relative humidity, and 0.16 MPaG using a pressure cooker tester was measured. 2 (%), 100 x (Y 1 -Y 2 ) / Y 1 is the relative fluorescence intensity decrease rate (%).

11. The Y 1 The phosphor powder according to claim 10, wherein the luminance distribution is 150% or more.

12. 3. The phosphor powder according to claim 1, wherein a reduction rate of absorptance of the phosphor powder for light having a wavelength of 455 nm is 5.0% or less when measured by the following method 3. (Method 3) The absorptance of the phosphor powder with respect to light having a wavelength of 455 nm measured using a spectrophotometer is Z 1 (%), and the absorptivity of the phosphor powder with respect to light having a wavelength of 455 nm after 53 hours of holding 5 g of the phosphor powder under an atmosphere of 130° C., 98% relative humidity, and 0.16 MPaG using a pressure cooker tester was determined as Z 2 (%), 100 x (Z 1 -Z 2 ) / Z 1 is the absorption rate reduction rate (%).

13. Said Z 1 The phosphor powder according to claim 12, wherein the content is 90.0% or more.

14. A composite comprising the phosphor powder according to claim 1 or 2 and a sealant that seals the phosphor powder.

15. The composite according to claim 14, wherein the sealing material comprises one or more selected from the group consisting of a silicone resin, an epoxy resin, a urethane resin, glass, and ceramics.

16. A light emitting element that emits excitation light; The composite of claim 14 which converts the wavelength of the excitation light; A light emitting device comprising:

Citation Information

Patent Citations

  • Phosphor, light-emitting device, illumination device and image display device

    JP2019077800A